2015
DOI: 10.1371/journal.pone.0130092
|View full text |Cite
|
Sign up to set email alerts
|

Infection with Salmonella enterica Serovar Typhimurium Leads to Increased Proportions of F4/80+ Red Pulp Macrophages and Decreased Proportions of B and T Lymphocytes in the Spleen

Abstract: Infection of mice with Salmonella enterica serovar Typhimurium (Salmonella) causes systemic inflammatory disease and enlargement of the spleen (splenomegaly). Splenomegaly has been attributed to a general increase in the numbers of phagocytes, lymphocytes, as well as to the expansion of immature CD71+Ter119+ reticulocytes. The spleen is important for recycling senescent red blood cells (RBCs) and for the capture and eradication of blood-borne pathogens. Conservation of splenic tissue architecture, comprised of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 50 publications
1
13
1
Order By: Relevance
“…It has been reported that S. typhimurium mainly attacks the intestine after it infects mice, which could induce the dysfunction of gastrointestinal tract and the damage of gastrointestinal mucous membrane, were consistented with our results [22], [23]. After infected with S. typhimurium, www.wjir.org most of mice have a systemic inflammatory response and an enlarged spleen [24]. Since S. typhimurium is a type of facultative intracellular pathogen, it could live in the macrophage [25], induce the apoptosis of macrophage, and release of mature proinflammatory cytokines, which could lead to the decrease of the macrophage ratio [26].…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that S. typhimurium mainly attacks the intestine after it infects mice, which could induce the dysfunction of gastrointestinal tract and the damage of gastrointestinal mucous membrane, were consistented with our results [22], [23]. After infected with S. typhimurium, www.wjir.org most of mice have a systemic inflammatory response and an enlarged spleen [24]. Since S. typhimurium is a type of facultative intracellular pathogen, it could live in the macrophage [25], induce the apoptosis of macrophage, and release of mature proinflammatory cytokines, which could lead to the decrease of the macrophage ratio [26].…”
Section: Discussionsupporting
confidence: 92%
“…Inflammatory response plays an important role in the pathological damage such as liver fibrosis, intestinal inflammation, and splenomegaly during schistosomiasis. Macrophages, as one kind of important immunoregulatory cell, play an irreplaceable role in the process of inflammatory reaction as well as the pathological damage process of the spleen (27). Therefore, the in-depth study of macrophage-related inflammation is extremely important to clarify the pathogenesis of schistosomiasis characterized by splenomegaly.…”
Section: Discussionmentioning
confidence: 99%
“…However, based on our work, it would be profitable and interesting to examine the impact of brucellosis on other infectious and noninfectious diseases in the regions where it is common. It has been recently reported (21) that, like infection with Brucella, chronic infection of mice with Salmonella enterica serovar Typhimurium induces a significant decline in the proportions of CD169 ϩ MMMs, suggesting that MZ alteration by chronic bacterial infection could be a common occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (17)(18)(19)(20)(21) investigating the impact of infection on MZ macrophage populations have performed only qualitative analyses by comparing their distribution by immunohistology. This approach does not allow for a fine comparison between several experimental conditions.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation